2016
DOI: 10.1039/c5rp00179j
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive apprenticeship as a vehicle for enhancing the understanding and functionalization of organic chemistry knowledge

Abstract: This paper presents a pedagogical experiment with parallel groups through which the effectiveness of the cognitive apprenticeship model of dealing with the teaching topic Carboxylic acids and their derivatives was compared with the traditional approach to the elaboration of this topic. This experiment featured the participation of 241 students aged 17, attending their third year of grammar school, natural sciences stream. The experimental group consisted of 118 students, whereas the control group was made up o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 40 publications
(36 reference statements)
2
13
0
Order By: Relevance
“…In this paper, we focus on the understanding of nucleophiles. The research literature supports the notion that nucleophiles and electrophiles are not equally understood (Strickland et al, 2010;Bretz, 2015, 2016;Putica and Trivic, 2016) with learners being more successful in identifying and explaining nucleophiles. While organic chemists may view these two entities as a combination, we note that learners need a more foundational understanding of each as they develop understanding of the relationship between the two.…”
Section: Understanding Of Nucleophilessupporting
confidence: 55%
“…In this paper, we focus on the understanding of nucleophiles. The research literature supports the notion that nucleophiles and electrophiles are not equally understood (Strickland et al, 2010;Bretz, 2015, 2016;Putica and Trivic, 2016) with learners being more successful in identifying and explaining nucleophiles. While organic chemists may view these two entities as a combination, we note that learners need a more foundational understanding of each as they develop understanding of the relationship between the two.…”
Section: Understanding Of Nucleophilessupporting
confidence: 55%
“…They explicitly talked about how learning in the same space with other learners gave them the ability to check in with seat mates about the information coming at them. Their observation has some grounding in the literature on distributed cognition and cognition as communication. , Breaking up presentations into smaller chunks and making routine use of breakout rooms to encourage processing of information and crosstalk would be valuable. Texting “during class”, which most instructors discourage for in-person settings, could be the online alternative to leaning over to check-in about content with one’s neighbor.…”
Section: Implications For Instructionmentioning
confidence: 99%
“…Several studies suggested that by combining the learning strategies such as constructivism with CAM could increase students' understanding of the concept of the subject matter. (García-Cabrero, Hoover, Lajoie, Andrade-Santoyo, Quevedo-Rodríguez & Wong, 2018;Putica & Trivic, 2016;Saadati, Tarmizi & Ayub, 2015;Kuo et al, 2012;). Thus, this would support the students' HOTS.…”
Section: Cognitive Apprenticeship Model (Cam)mentioning
confidence: 99%